PENGARUH BRAND IMAGE DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Tekun Jatinangor) - Fauziah Husna; Erna Maulina; Raden Marsha Aulia Hakim (JURNAL LENTERA BISNIS, 2024)
This research aims to observe the influence of brand image and sales promotion on purchasing decisions at Tekun Jatinangor outlets. The method used is quantitative with a survey method. By distributing research questionnaires using Google Form, data was obtained using a Likert scale which was processed and tested using SPSS 25. The population is people who have made Tekun purchases in Jatinangor so the population size is unknown. Samples were taken using non-probability sampling, namely purposive sampling. Due to the uncertain population size, the sample size was calculated using the Cochran formula to obtain 100 respondents. From the results of research and hypothesis testing, it can be obtained that brand image and sales promotion have a positive effect on purchasing decisions with a sig. 0,000. Sales promotion has a positive effect on purchasing decisions with a sig value. 0.010. Brand image and sales promotion have a positive effect on purchasing decisions with a significance value of 0.000. The results of this research show that the R square coefficient value is 54.9%. Key words: Brand image, Sales promotion, Purchase Decisions